Dietary intake of overweight and obese women during pregnancy - Koivuniemi, Ella (fi=Turun yliopisto|en=University of Turku|, 2016)
Diet during pregnancy is an important determinant of the health of both the mother and the child. Unbalanced dietary intake during pregnancy may lead to high gestational weight gain and complications including gestational diabetes. Timely information of the dietary intake particularly in overweight and obese pregnant women is needed to improve the nutrition counselling in maternal clinics. The primary aims of this thesis are to determine the dietary intake of overweight and obese pregnant women in relation to the current dietary recommendations and changes in mothers’ diets between early and late pregnancy. In addition, differences in dietary intakes between overweight and obese women and relations between dietary intake and weight will be studied. The data consist of 99 women participating in an on-going mother-child dietary intervention study. Energy and nutrient intakes were calculated from three-day food diaries with a computerized software in early (pregnancy week median 14.0, IQR 11.4–15.4) and late pregnancy (median 35.4, IQR 33.4–36.1). Of the women (pre-pregnancy BMI 29.4 kg/m2, IQR 26.8–32.2), 51.5% were overweight (pre-pregnancy BMI 25.0-29.9 kg/m2) and 48.5% were obese (pre-pregnancy BMI ≥30 kg/m2). The energy intake of the women did not increase statistically significantly between early (7.9 MJ, IQR 6.7–9.2) and late pregnancy (8.1 MJ, IQR 6.9–9.7). Intakes of energy-yielding nutrients were mostly in accordance with the Finnish dietary recommendations. The carbohydrate intake decreased (P=0.011) between early (46.5 percentage of energy intake (E%), IQR 42.3–50.9) and late pregnancy (44.3 E%, IQR 40.2–49.5), ending up lower than recommended (45-60 E%) in late pregnancy. In addition, the intake of dietary fibre was below the recommendation in both time points (20.0 g, IQR 15.3–25.9 and 18.8 g, IQR 14.9–25.1 respectively; recommendation 25-35 g). The total fat intake increased between early and late pregnancy (33.5 E%, IQR 29.6–38.3 vs. 36.0 E%, IQR 32.2–41.0; P<0.01) remaining within the recommended range (25-40 E%). However, the intake of saturated fatty acids was higher than recommended at both time points (12.2 E%, IQR 10.1–13.6 and 12.8 E%, IQR 11.1–14.3 respectively; recommendation < 10 E%). The dietary intakes of most micronutrients were in accordance with the recommendations but the intakes of folate and vitamin D were insufficient. The intake of folate was 235 μg (IQR 193–283) in early pregnancy and 245 μg (IQR 178–302, recommendation 500 μg) in late pregnancy. As for vitamin D, the intake increased significantly (P=0.028) from 6.5 μg (IQR 4.6–10.1) in early pregnancy to 8.4 μg (IQR 5.3–12.1, recommendation 10 μg) in late pregnancy. However, 95% of the women used dietary supplements in early pregnancy and 93% used them in late pregnancy. No significant differences were found between the dietary intakes of overweight and obese women. The body weight in both early and late pregnancy correlated positively with the intakes of energy, carbohydrates, total fat, saturated fatty acids and monounsaturated fatty acids in late pregnancy. The results indicate that the dietary intakes of Finnish overweight and obese pregnant women are mostly in accordance with the dietary recommendations but more attention should be paid to the excess intake of saturated fatty acids and the low intakes of fibre, folate and vitamin D. Nutrition counselling during gestation should focus on these factors even more in order to improve the diet quality of the pregnant women, and thus reduce the risks related to inadequate diet intake.